HANTARAN TRADITTION IN MARRIAGE CULTURAL OF MALAY CITYZENS AT PEKAN HERAN VILLAGE WEST RENGAT SEBDISTRICT INDRAGIRI HULU REGENCY - Arisandi, Denopri; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Tradition is a pattern of behavior that engendered to the culture in communitypeople. This is the result of that community it self. Every community have owncharecteristic that appear from life process that’s called tradition. Inside of thecommunity at Pekan Heran village West Rengat Sebdistrict Indragiri Hulu Regency,will do marriege with present. This present tradition is one of marreige process thatgiven by fiance to fiance family like some useful stuff and some money to help outand responsibility from fiance in their relatinsho later.This study intended to determine how the public’s understanding of the processof present tradition that has undergrone a shift in hantaran as well as the factors thatcaused it.Appereance of globalization in the community of Indragiri Hulu is threat foretenity and continuity malay characteristic of Indragiri Hulu for long time ago. Theneven increasing number of population and the entry of other people characteristiceffect, education factor, economy factor and advance technology is also need faithand devotion in applying especially young people will be lead future os society. Withthe advance by the various transformation in various sectors many of the values andtraditions that were forgotten and almost lost and tend to shift from society of malay.Keywords: Hantaran Tradition, Malay Cityzens, Shifting Value.